Kontribusi Ayat-Ayat Bersuci di Era Covid 19 Terhadap Kesehatan (Telaah Atas Tafsir Jami’ al-Ahkam al-Qur’an Karya al-Qurtubi) - Abdul Basid (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2021)
Cleansing or cleaning oneself is one of the efforts of humans to protect themselves, not only because of the need for ritual worship, but also for health interests. Cleaning up is currently a matter of great concern considering that humanity is currently struggling together to deal with the Covid-19 virus, which is known to be very easily transmitted through contact with surfaces and air. In this paper, we will examine the contribution of the Qur'anic verse which talks about personal hygiene or purification of health education in the era of the Covid-19 pandemic as it is today. This research is a research library research which will collect data related to the commandment of purification according to the al-Qurthubi commentary review, then will analyze the contribution of verses to health education in the Covid-19 era.The results of the study found that the commandment to purify in Q.S al-Maidah verse 6, which is basically to perform a worship, has a great value as well in facing the Covid-19 pandemic era as it is today. In addition to being able to make someone fearful when he is always in a holy state, he will also maintain his physical cleanliness, and will always be in a healthy state and also able to avoid the Covid-19 virus which is very easy to spread.